Renovering av kulturhistoriskt värdefull byggnad med hänsyn till termisk komfort och dagsljus - Sandin,Love (TVBH -5000, 2025)
This report explores how a renovation of a heritage building in Malmö performs according to thermal comfort and daylight conditions with challenges related to conservation requirements and modern building standards. The goal is to analyse a presented floor plan to see what conflicts arise between Swedish building law and regulations, and efforts to modernise aging culturally important buildings. The certification system Miljöbyggnad was also used to explore higher above required levels. The method used was simulation of the building in IDA ICE and VELUX Vizualiser to explore how the proposed renewal of the industrial building would affect daylight conditions and thermal comfort. The results show that during the winter small amounts of insulation is sufficient for good operative temperature but during the summer the buildings large open windows create difficulties keeping temperatures under required limits. External sun shading was able to meet required values but clashes directly with recommended ways of not squandering the buildings cultural values. Daylight conditions were good in almost the entirety of the building except some of the centre rooms due to the building’s cubic nature. Light colour and smoother textures helped reach good levels of daylight but also stand in conflict with restoring the building in a way that honours its heritage.
Keywords: Kulturhistoriska byggnader; K-märkt; Renovering; Tegelfasad; Tilläggsisolering; Innemiljö; Termisk komfort; Energieffektivisering; Simulering; Dagsljus; IDA-ICE; Miljöbyggnad; Industrilokal.